“Oxum está vendo isso aí”: Gênero e relações de poder no terreiro Santa Bárbara e mestre Zé dos Anjos em Campina Grande/PB - Leite, Maria Luiza Pereira (2017)
This work consists of an effort to construct a narrative of an ethnographic nature, intertwining issues that focus on the debate on gender, from the spiritual / political / academic experience that began in May 2013 in the Umbanda and Jurema in Campina Grande, focusing mainly on the constitution and dynamics of one of the oldest and most traditional terreiros in the city, Terreiro Santa Bárbara and Mestre Zé dos Anjos, located in the neighborhood of Ramadinha II. The methodological proposal is constructed in the field and with it, using some combined research instruments: participant observation (or "observant participation") with field journal record; the thematic life history or topical life history; and the semi-structured interview – the last one aiming at recording the life trajectory of the leadership of the said terreiro, Mother Carminha da Ramadinha, Ialorixá and Juremeira known and respected among the Afro-Amerindian religion community of the city and region. As a writing course, I choose to follow the path of the production of situated knowledge, and as such, I take first-person writing as a political and epistemological option, as I perceive as absolutely necessary the exposition of my insertion process in the field, in its difficulties, surprises, fissures, and contradictions. One of the theoretical questions addressed in this work is to discuss how the gears of the gender discourse operate in the terreiro – space of such a diverse and delicate reality, here understood as a social marker of difference intersecting with class, race, religiosity, generation. Finally, I make use of the concept of the sexual division of labor, a discursive, social and political process, which historically fixed the place of the domestic as naturally feminine, to discuss some aspects observed in the field, such as when, during ritual work, women have the responsibility to take on all the kitchen tasks, as well as all the functions related to the domestic sphere, an essential space for all processes related to religion, but yet not enough discussed in the studies on Afro-Amerindian religiosities.